MTOR inhibitors for treatment of low-risk prostate cancer. (August 2018) - Liss, Michael A.; Rickborn, Lanette; DiGiovanni, John; Bacich, Dean; DeGraffenried, Linda A.; Parihar, Manish; Thompson, Ian M.; Sharp, Zelton Dave
Abstract: Prostate cancer incidence increases with age; along with many other cancers, it could be considered a disease of aging. Prostate cancer screening has led to a significant proportion of men diagnosed with low-grade, low-stage prostate cancer who are now more likely to choose an active surveillance strategy rather than definitive treatments. Definitive treatment, such as surgery and radiation therapy, is useful for high-grade disease; however, because of the low long-term risk of progression of a low-grade disease and side effects of surgery and radiation, these treatments are less commonly used for low-grade disease. While five alpha reductase inhibitors have been shown to reduce the risk of cancer detection on subsequent biopsies for men on active surveillance, no medications have been proven to prevent progression to high-grade disease. mTOR pathways have long been known to influence prostate cancer and are targets in various prostate cancer patient populations. Low-dose mTOR inhibition with rapamycin has shown promise in pre-clinical models of prostate cancer and appear to affect cellular senescence and immunomodulation in the aging population. We hypothesize that low-dose mTOR inhibition could reduce progression of low-grade prostate cancer patients, allowing them to remain on active surveillance.